SA118. Intranasal Oxytocin Does Not Modulate Jumping to Conclusion: S in Schizophrenia: Potential Interaction With Baseline Social Functioning - Caravaggio, Fernando (Schizophr Bull, 2017)
Background: Oxytocin is a neuropeptide implicated in maintaining trust and affiliative behaviors in humans. Currently, there is great interest in exploring the therapeutic potential of oxytocin as an adjunct to conventional antipsychotic treatment for improving clinical and social cognitive symptoms in patients with schizophrenia. It has been well established that patients with schizophrenia show deficits in probabilistic reasoning tasks such that they quickly jump to conclusions without sufficient evidence. Since performance on this task is related to activation of prefrontal areas also implicated in social cognition, we explored whether intranasal oxytocin could improve probabilistic reasoning performance in stable medicated patients with schizophrenia. Methods: Forty-three male, medicated patients with schizophrenia (Mean Age ± SD: 40.81 ± 11.44) and 16 matched healthy controls (Mean Age ± SD: 30.38 ± 9.85) participated in a double-blind, placebo-controlled, crossover study. Participants were required to complete the “Jumping to Conclusions” probabilistic reasoning task on 2 separate study visits (minimum 20 days apart). For each study visit, participants were randomized to receive either intranasal oxytocin (50 IU in solution) or intranasal placebo (saline). Results: Consistent with previous findings, patients with schizophrenia showed deficits in probabilistic reasoning, jumping to conclusions more often than healthy controls, t(57) = 2.78, P = .007. Oxytocin did not significantly change probabilistic reasoning performance in patients, t(42) = −1.11, P = .27, nor in healthy controls, t(15) = −.62, P = .55). However, there was great variability in change in performance given oxytocin in patients. Exploratory analyses found that patients with lower bassline social functioning, as assessed by the Social Functioning Scale, showed more change on the probabilistic reasoning task given oxytocin, characterized by a reduced tendency to “jump to conclusions.” Conclusion: Acute oxytocin does not appear to modify probabilistic reasoning in healthy controls and patients with schizophrenia. However, future studies should explore the potential confound of baseline social functioning.